(3JfejI GdegGQGJ JWHjbjG(B-(3eONd LOjO ddJaGhVs - (3YdG YHO GdaJGM(B, (3QLHs ((3GdbGgQI(B:s (3OGQ GdeQjN(B,s, 2006)
(3GdgOa ef OQGSI Yde GdJaGhV GdSjGSj hGdGLJeGYj ef NdGd efXhQ GdSjchdhLj, WHjYI GdGJUGd GdJaGhVj, GdeMJhjGJ GdGSGSjI ddJaGhV, cja jecfc GNJjGQ aQjb GdJaGhV, GSJQGJjLjGJ GdJaGhV, JcfjcGJ GdJaGhV, JfejI egGQGJ GdJaGhV GdCSGSjI, GdJaGhV hGdeDKQGJ GdNGQLjI, SjchdhLjI GdJaGhV cCSdhH CeKd dEOGQI GdCReGJ, HQGeL JWHjbjI dJfejI egGQGJ GdJaGhV hGdJOQjH, ehGba JWHjbjI JaGhVjI ddJOQjHs
Keywords: (3GdEJUGdGJs; (3GdEOGQIs; (3GdeSGheIs